2019
DOI: 10.1021/acs.langmuir.9b01373
|View full text |Cite
|
Sign up to set email alerts
|

Protein–Nanoparticle Interactions: What Are the Protein–Corona Thickness and Organization?

Abstract: Protein adsorption on a surface is generally evaluated in terms of the evolution of the proteins’ structures and functions. However, when the surface is that of a nanoparticle, the protein corona formed around it possesses a particular supramolecular structure that gives a “biological identity” to the new object. Little is known about the actual shape of the protein corona. Here, the protein corona formed by the adsorption of model proteins (myoglobin and hemoglobin) on silica nanoparticles was studied. Small-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 47 publications
1
60
0
Order By: Relevance
“…However, one fundamental factor needs to be highlighted: aggregation of the NPs. Indeed, gold NPs mixed with proteins did not undergo any noticeable aggregation while SiNPs tend to aggregate when mixed with proteins [64]. So, in this study, an additional explanation can be proposed.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…However, one fundamental factor needs to be highlighted: aggregation of the NPs. Indeed, gold NPs mixed with proteins did not undergo any noticeable aggregation while SiNPs tend to aggregate when mixed with proteins [64]. So, in this study, an additional explanation can be proposed.…”
Section: Discussionmentioning
confidence: 57%
“…Increasing the curvature allows to optimize the packing on the surface ( Figure 5B), but another type of steric hindrance can be identified for very small particles. When the size of the NPs is in the range of the size of the proteins, the formation of protein nanoparticle aggregates, recently observed by neutron scattering [64,74] leads to the formation of a porous network that renders a significant proportion of the NP surfaces inaccessible ( Figure 5C). We must notice that such an optimal ratio of 10 between local curvature and polymer size was already identified in synthetic polymer adsorption on rough surfaces [44,75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein corona may consist of tens or hundreds of proteins. They alter the physicochemical properties of NPs, such as size, zeta potential, morphology, and aggregation state (Gebauer et al, 2012;Su et al, 2012;Glancy et al, 2019;Marichal et al, 2019). At the same time, the protein corona also alters the interactions between NPs and biological systems and modulates the kinetics, transport, and reactivity of NPs Lesniak et al, 2012;Walkey et al, 2012Walkey et al, , 2014Tenzer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the protein-gold nanoparticle interactions and protein corona (PC) formed in the presence of Au NPs alter the physiological properties and provides "biological identity" to the newly formed AuNP-PC complex. [70][71][72][73] Renault et al 70 reported the protein adsorption (myoglobin and hemoglobin) on the surface of silica nanoparticles (SNPs) and formation of an organized but discontinuous monolayer of proteins around the SNPs. Monticelli and colleagues 71 reported the importance of the ligand conformation on the NP-protein interaction.…”
mentioning
confidence: 99%